2005
DOI: 10.1177/107110070502601210
|View full text |Cite
|
Sign up to set email alerts
|

Arthrogenic Muscle Inhibition in the Leg Muscles of Subjects Exhibiting Functional Ankle Instability

Abstract: Depressed H:M ratios in the injured limb suggest that arthrogenic muscle inhibition is present in the ankle musculature of patients exhibiting functional ankle instability. Establishing and using therapeutic techniques to reverse arthrogenic muscle inhibition may reduce the incidence of functional ankle instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
105
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 40 publications
7
105
0
2
Order By: Relevance
“…43 This a-c coactivation is an autonomic process that maintains the muscle-spindle sensitivity needed for dynamic stability. Regarding neuromuscular dysfunction in individuals with CAI, researchers [44][45][46] have explored dynamic stability by measuring a motor-neuronpool excitability.…”
Section: Discussionmentioning
confidence: 99%
“…43 This a-c coactivation is an autonomic process that maintains the muscle-spindle sensitivity needed for dynamic stability. Regarding neuromuscular dysfunction in individuals with CAI, researchers [44][45][46] have explored dynamic stability by measuring a motor-neuronpool excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers 18,22 have reported decreased excitability in the fibularis longus of patients with chronic pathologic ankle conditions. They have suggested that decreased spinal reflex excitability of the fibularis longus is important, 18,32 as this muscle may slow ankle inversion and decrease the incidence or extent of injury related to lateral ankle sprains.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas differences between outcomes in spinal reflex excitability of the fibularis longus in previous studies commonly were hypothesized to be due to different lengths of time since injury, 46 these differences also may be due to variations in the nervous system response to injury in individual CAI patients. Many researchers 18,22,45,46 have evaluated spinal reflex excitability after ankle injury in relatively small cohorts of injured patients (N , 30). In future studies with larger sample sizes, investigators may be able to determine if subgroups that display particular clusters of similar neurophysiologic alterations, which may manifest in specific patterns of spinal reflexive and corticospinal adaptations, can be identified after ankle injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations